Clinical impact of high density mapping in atypical atrial flutters ablation: outlining critical circuits in complex atrial tachycardias. (14th October 2021) - Di Cori, A; Mazzocchetti, L; Parollo, M; Della Volpe, S; Barletta, V; Cellamaro, T; Segreti, L; Viani, S; De Lucia, R; Paperini, L; Giannotti, M; Canu, A; et al.
Abstract: Introduction: Mapping and ablation of atypical atrial flutter (AFL) continue to be a challenge for clinical electrophysiologists. The advent of high-density (HD) mapping has allowed the generation of electro-anatomic maps with a very high resolution level. Purpose: In this single center retrospective analysis, we evaluated the clinical impact of the ultra HD activation sequence mapping compared with the standard low density (LD) ablation catheter mapping technique in the treatment of AFLs. Methods: We performed a 7 years-single center retrospective analysis of patients undergoing radiofrequency ablations (RFA) for right and left atypical AFL. We evaluated procedural and clinical outcomes of patients approached with a Low Density (LD) electro-anatomical (EAM) strategy compared with patients mapped with new automatic multipolar HD Mapping (HD Group). Results: Seventy-five patients were included. Patients were almost male (60%), relatively old (65±8 years), with a moderate CHA2DS2Vasc score (2.3±1.3), a preserved ejection fraction (58±6) and moderate atrial dilatation (44±7 mm). Baseline clinical characteristics were comparable between groups (p=NS). Among 88 AFLs, 10 (11%) were located in the right and 78 (89%) in the left atrium, including 22 (28%) roof dependent and 37 (47%) mitral dependent (p=NS). Regarding procedural outcomes, Sinus rhythm restoration during ablation was more frequently observed in the HD Group (79% vs 56%, p=0.037), even if no differences in mapping time, procedural time and radiological dose were observed (p=NS). Freedom from AFL/atrial fibrillation (AF) at 1-year was lower in the HD Group (83% vs 45%, p=0.009) with an increased trend for AF recurrences during long term follow-up (17% vs 23% at 1 and 3-years respectively, p=0.059). At the multivariate analysis, HD map (OR 0, 17; 95% CI 0, 04–0, 66) and younger age (OR 1, 09; 95% CI 1, 01–1, 19) were identified as independent predictors of ablation success at 1 year. Conclusions: Acute procedural success of ablation of atypical atrial flutter is higher in case of HD mapping strategy. Patient age and HD strategy resulted independent predictors of overall atrial arrhythmias recurrences. During follow-up, AFL recurrences are rare beyond 12 months, differently from AF which continues to show increasing trends. Funding Acknowledgement: Type of funding sources: None.